Wildlife medicine and rehabilitation - Meredith, Anna.; Keeble, Emma J. (London : Manson Pub., 2011)
Veterinarians increasingly encounter wildlife casualties in practice and have a duty of care for the welfare of the animals. This comprehensive and easy-to-use self assessment book contains some 208 clinical cases with 325 illustrations. It has been compiled by authors with a wide range of experience and expertise in this area. Common conditions seen in wildlife species are covered with cases from Europe, North America, the Middle East and Australia. The selection of cases is presented randomly and covers scenarios relevant to most readers. The book is of value to veterinarians in practice and training and to all those working directly with wildlife who wish to expand their knowledge in this field.
Flamingos Swans Ducks Geese Buzzards Kestrels Sparrowhawks Falcons Vultures Eagles Owls Blackbirds Greenfinches Chaffinches Ospreys Guillemots Curlews Gulls Pheasants Lorikeets Herons Bustards Coots Moorhens Cuckoos Doves Squirrels Hares Rabbits Foxes Otters Badgers Raccoons Mink Hedgehogs Seals Dolphins Whales Manatees Hippopotami Oryx Deer Gorillas Elephants Bats Shrew Echidna Wallabies Possums Kangaroos Koalas Reptiles Miscellaneous.
Includes index
Keywords: Wildlife diseases; Wildlife rehabilitation; Animal Diseases -- diagnosis; Animal Diseases -- therapy; Animals, Wild